Interactive Approaches in Teaching Values Education: Applying ‎Qualitative Methods to Study Religious Education - Kuswandi, Iwan; Ridwan, M; Surur, Miftahus; Shohenuddin, S; AR, Muhammad Misbahudholam; Jamilah, J (International Journal of Basic and Applied Sciences, 2025)
The internalization of the Aswaja teachings within Nahdlatul Ulama, combined with Islamic ‎values and Muhammadiyah teachings within the Muhammadiyah organization, often occurs in ‎the realm of practical education. This article examines the internalization efforts undertaken by ‎both organizations within the Malaysian educational landscape, with particular attention to the ‎non-formal education Guidance Centers affiliated with the Indonesian School in Kuala ‎Lumpur, Malaysia. Furthermore, this study employed a qualitative, case-based method. Data ‎were collected through observation, interviews, and documentation. Furthermore, the analysis ‎employed an interactive model, which combines data collection, condensation, presentation, ‎and verification of conclusions. The research findings indicate that internalization carried out in ‎guidance centers affiliated with Nahdlatul Ulama includes the recitation of Yasin, the Tahlil ‎ritual, and the practice of Salawat. A similar approach has been adopted by Muhammadiyah, ‎whose internalization and actualization of the teachings of Surah Al-Ma’un are more focused on ‎the dimension of social concern, while also embodying faith through hygiene practices‎.